(untitled) (Journal of Economic Research & Business Administration, 2015)
Accounting outsourcing becomes relevant today. In the current competitive environment of business, some companies accounting outsourcing was an opportunity to reduce the cost of maintaining the state of accountants, for others – an effective way to improve and optimize the process of accounting. Outsourcing – is the transfer of the management functions to a third-party organization or companies. Outsourcing bookkeeping services involves transmission of bookkeeping specialized companies that perform bookkeeping dozen organizations, reporting to public authorities, payroll, and perform many other extras. In Kazakhstan (especially in Almaty) outsourcing accounting or payroll is becoming increasingly popular. Qualifi ed accountants in Almaty, with extensive practical experience, not so much, and training young professionals takes time. In this regard, many entrepreneurs have recourse to come accountants that generates risks of incurring losses in the form of penalties, due to their non-prescribed in the contract liability. Thus, accounting outsourcing is a good option in terms of price / quality. It may include outsourcing accounting or payroll and bookkeeping enterprise.